2018
DOI: 10.1111/his.13522
|View full text |Cite
|
Sign up to set email alerts
|

Solid papillary breast carcinomas resembling the tall cell variant of papillary thyroid neoplasms (solid papillary carcinomas with reverse polarity) harbour recurrent mutations affecting IDH2 and PIK3CA: a validation cohort

Abstract: We validated the presence of IDH2 R172 hotspot mutations and PIK3CA hotspot mutations in 100% and 67% BPTCs tested, respectively, and documented absence of IDH2 R172 mutations in SPCs. These findings confirm the genotypical-phenotypical correlation reported previously in BPTC, which constitutes an entity distinct from conventional SPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 24 publications
3
56
0
Order By: Relevance
“…To further highlight the lack of consensus on the terminology of this entity, a recent study used 2 terms: "solid papillary breast carcinomas resembling the tall cell variant of papillary thyroid neoplasms" and "solid papillary carcinomas with reverse polarity" [19]. Other authors [18] have proposed a new terminology "tall cell variant of papillary breast carcinoma," in an attempt to avoid confusion as well as unnecessary ancillary studies aimed at excluding the association of this entity with thyroid PC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To further highlight the lack of consensus on the terminology of this entity, a recent study used 2 terms: "solid papillary breast carcinomas resembling the tall cell variant of papillary thyroid neoplasms" and "solid papillary carcinomas with reverse polarity" [19]. Other authors [18] have proposed a new terminology "tall cell variant of papillary breast carcinoma," in an attempt to avoid confusion as well as unnecessary ancillary studies aimed at excluding the association of this entity with thyroid PC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 3 studies [15,19,20] showed an association between BTRTPC and the isocitrate dehydrogenase 2 gene (IDH2) mutations. These mutation has been described in gliomas, acute myeloid leukemia, and cholangiocarcinoma [26], but their possible role in breast carcinogenesis has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 The genomic characterisation of rare breast cancer types has demonstrated that their histological heterogeneity is paralleled by vast genetic heterogeneity. 5,6 Work by our group and others has led to the identification of pathognomonic genetic alterations in rare breast cancers, such as the MYB-NFIB fusion gene or MYBL1 rearrangements in adenoid cystic carcinoma, 6-10 the IDH2 R172 hotspot or TET2 mutations concurrently with PIK3CA or PIK3R1 mutations in solid papillary carcinomas with reverse polarity, 11,12 and HRAS Q61 hotspot mutations concurrently with PIK3CA mutations in ER-negative adenomyoepitheliomas. 13 The analyses of mucinous carcinomas, [14][15][16] however, have not resulted in the identification of a pathognomonic genetic alteration; rather, these studies have demonstrated that mucinous carcinomas lack PIK3CA mutations, concurrent 16q losses and 1q gains, which are characteristic features of common forms of ER-positive breast cancers.…”
Section: Introductionmentioning
confidence: 99%